Analysis of Learning Outcome Elements in Islamic Religious Education Learning: A Study of Dzawin Nur's YouTube Content - Dzaki Alfajri; Umiarso; Nafik Muthohirin (Ta'dib: Jurnal Pendidikan Islam, 2024)
This study aims to identify and analyze the elements of Islamic religious education learning outcomes conveyed through Dzawin Nur's YouTube channel.  This research method uses a descriptive qualitative approach. The data analysis technique is a content analysis technique used to evaluate and classify the videos published on YouTube. The research data source was obtained through Dzawin Nur's YouTube channel itself, where the data taken from this source are elements of Islamic religious education, namely akidah, fiqh (worship), and morals. The data collection technique used in this research is documentation in the form of Dzawin Nur's content on his YouTube channel. The results showed that elements of Islamic religious education learning outcomes, such as belief, worship, and morals, were explained in Dzawin Nur's YouTube channel. On his YouTube channel, the element of faith presents material related to the oneness of Allah SWT, where Dzawin Nur invites viewers to believe in the oneness of Allah SWT and ask only Allah SWT. In addition, the worship element and carrying out worship are discussed as stated in the Al-Quran and hadith. The worship discussed in the content is the problem of learning. The obligation to learn is a devotion of a Muslim that has been regulated and ordered in the hadith of the prophet. Therefore, learn because learning is an order contained in the hadith of the prophet Muhammad. And finally, the moral element, where this element is mentioned a lot in Dzawin Nur's videos. One of the moral elements mentioned in his videos is behavior and attitude when making friends. In this case, we are presented by the creator with ethics when choosing and making friends well and also ethics in getting along with others.